Mediating Culture(s) in Foreign Language Teaching - Mădălina Tvardochlib (Linguaculture)
What one understands culture to be trickles down into the practices of teaching culture. The establishment of cultural studies and globalization as the dominant paradigms lead to a shift in the aims of foreign language teaching due to teachers and students acknowledging new societal realities. Culture can no longer be fathomed only as high or national culture but rather as a sum of daily practices and routines, as well as interpretative patterns regarding art, literature, politics and so on. The above-mentioned aspects have to be taken into consideration in a discourse and student-centered teaching approach. Culture-based learning resorts to a broader and more nuanced perspective of the meaning of culture. This paper aims to examine past and present traditions of integrating cultural aspects in class, as well as assess students’ previous experience in dealing with cultural aspects in order to establish a broad view of the status quo. Furthermore, the paper will consider a range of possible means to integrate culture-based learning while teaching foreign languages and consider the practical implications of using the method. As this approach fosters empathy and cross-cultural communication, culture-based learning can prove a stepping stone to developing valuable soft skills, especially in an academic setting.